In vitro and in vivo Effects of a Single Dose of Bupivacaine 5% on Donkey Chondrocytes - Hussein, Kamal; Abdelbaset, Abdelbaset Eweda; Sadek, Ahmed Abdelrahiem; Noreldin, Ahmed (Frontiers in Veterinary Science, 2021)
Single intra-articular (IA) injection of long-acting local anesthetics such as bupivacaine is commonly used clinically for postoperative analgesia, in particular after arthroscopic surgery. Despite their widespread use, the side effects of IA bupivacaine on joint cartilage as well as hepatotoxic and nephrotpxic effects remain to be elucidated. The aim of this study is to assess the in vitro effect of bupivacaine 5% on donkey chondrocytes at different time points, in addition to the in vivo effects of a single IA bupivacaine injection on the middle carpal joint in a group of 10 clinically healthy adult male donkeys. In phase I, the effect of in vitro treatment with bupivacaine 5% or saline 0.9% on freshly isolated donkey chondrocytes for 30 minutes, 60 minutes, 24 hours, 48 hours, and 96 hours was investigated using MTT and Live/Dead assay. In phase II, in vivo effects of single injection of bupivacaine on the donkeys’ middle carpal joint were evaluated compared to saline 0.9%. Biochemical analysis of collected serum and synovia was performed. Additionally, articular cartilage damage was evaluated using radiography, computed tomography (CT), catabolic markers expression via quantitative polymerase chain reaction (qPCR), and histopathological examination 96 hours after injection. Our results showed that after 30-minutes exposure to bupivacaine 5%, the viability of donkey chondrocytes was 97.3 ± 4.4% and was not significantly affected at the indicated time points (n = 8, P < 0.05). No significant changes in biochemical analytes of serum and synovial fluid following IA bupivacaine injection were observed, compared to saline injection (n = 5 for each group, P < 0.05). Furthermore, in vivo IA injection of bupivacaine revealed no significant differences in radiography, CT scan, gene expression of cartilage catabolic biomarkers, and histopathological examination. These results provide an evidence for the safety of bupivacaine on the donkey cartilage.